Cardiovascular Risk Factors and Ischemic Heart Disease: Is the Confluence of Risk Factors Greater Than the Parts? A Genetic Approach. (June 2016) - Elosua, Roberto; Lluís-Ganella, Carla; Subirana, Isaac; Havulinna, Aki; Läll, Kristi; Lucas, Gavin; Sayols-Baixeras, Sergi; Pietilä, Arto; Alver, Maris; Cabrera de León, Antonio; Sentí, Mariano; Siscovick, David; et al.
Abstract : Background—: Cardiovascular risk factors tend to aggregate. The biological and predictive value of this aggregation is questioned and genetics could shed light on this debate. Our aims were to reappraise the impact of risk factor confluence on ischemic heart disease (IHD) risk by testing whether genetic risk scores (GRSs) associated with these factors interact on an additive or multiplicative scale, and to determine whether these interactions provide additional value for predicting IHD risk. Methods and Results—: We selected genetic variants associated with blood pressure, body mass index, waist circumference, triglycerides, type-2 diabetes mellitus, high-density lipoprotein and low-density lipoprotein cholesterol, and IHD to create GRSs for each factor. We tested and meta-analyzed the impact of additive (synergy index) and multiplicative (βinteraction ) interactions between each GRS pair in 1 case–control (n=6042) and 4 cohort studies (n=17 794) and evaluated the predictive value of these interactions. We observed 2 multiplicative interactions: GRSLDL ·GRSTriglycerides (βinteraction =–0.096; SE=0.028) and nonpleiotropic GRSIHD ·GRSLDL (βinteraction =0.091; SE=0.028). Inclusion of these interaction terms did not improve predictive capacity. Conclusions—: The confluence of low-density lipoprotein cholesterol and triglycerides genetic risk load has an additive effect on IHD risk. The interaction between low-density lipoprotein cholesterol and IHD genetic load is more than multiplicative, supporting the hazardous impact on atherosclerosis progression of the combination of inflammation and increased lipid levels. The capacity of risk factor confluence to improve IHD risk prediction is questionable. Further studies in larger samples are warranted to confirm and expand our results. Abstract : Supplemental Digital Content is available in the text.